Analysis of Risk Factors for Stunting Incidence in Children Under Two Years in Helebeik Village, Lobalain District, Rote Ndao Regency - Janur Chornelis Ndolu; Engelina Nabuasa; Mustakim Sahdan (Lontar : Journal of Community Health, 2022)
Several factors influence stunting in children under two: mother's upbringing, household characteristics, availability of clean water, and environmental sanitation. This study analyzed the risk factors for stunting in children under two years old in Helebeik Village, Lobalain District, and Rote Ndao Regency. This type of research was an analytic survey with a case-control study design. The population in this study was 218 children under two years old. The sampling technique used the proportional sampling method with 88 children under two years old, 44 children under two years old in the case group, and 44 other children under two years old in the control group. The results showed a significant relationship between hygiene practice, nursing practice, mother's education, number of families, type of floor, latrines, trash cans, and clean water with stunting, where the p-value <0.05. Meanwhile, there was no relationship between feeding practices and stunting, with a p-value of 0.05. Relevant agencies should monitor and control stunting in Baduta to minimize the incidence of stunting.